Application of Black Water from Vegetable Waste with Decomposers in Planting Media Based on Blotong on Growth and Yield of Water Spinach - Badriyah , Muflikhatul; Hariyono, Kacung (University of Jember, 2024)
Utilization of vegetable waste can be used as organic fertilizer such as black water. Black water from vegetable waste is used as fertilizer to increase the growth and yield of water spinach. Black water can be made by using a decomposer in the form of lumbricus sp and EM4 worms to help with the decomposition process. The planting medium of filter cake compost is an additive for soil amendments that support the availability of nutrients in plants. This study used the addition of decomposers EM4, rumen MOL, and Trichoderma sp. This research used a two-factor factorial with a completely randomized basic design (CRD) consisting of 2 factors and three replications. The interaction between the application of the black water decomposer and the filter cake media did not have a significant effect on all the observed variables. Likewise, with the single factor, the application of black water does not have a significant effect on all observed variables. The single factor in the treatment of using filter cake media has a substantial impact on all observational variables. The best treatment was on M3, comparing the composition using 20% filter cake planting media and 80% soil.